2022
DOI: 10.1101/2022.11.21.517316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allosteric communication between ligand binding domains modulates substrate inhibition in adenylate kinase

Abstract: Enzymes play a vital role in life processes; they control chemical reactions and allow functional cycles to be synchronized. Many enzymes harness large-scale motions of their domains to achieve tremendous catalytic prowess and high selectivity for specific substrates. One outstanding example is provided by the three-domain enzyme adenylate kinase (AK), which catalyzes phosphotransfer between ATP to AMP. Here we study the phenomenon of substrate inhibition by AMP and its correlation with domain motions. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…By contrast, ATP induces the closing of the LID domain, and the subsequent arrival of AMP induces the closing of the NMP domain. These observations suggest the existence of an endosteric effect whereas: the initial binding of AMP inhibits the binding of ATP, or the initial binding of AMP forms a less active conformation, as previously suggested, 51 or the ATP-induced closing of the LID domain induces the formation of a higher-affinity binding site for AMP. In the M2-ternary-AMP:ATP:AK complex, the LID domain is more tightly closed (Figure 2I, right) than in the M2-binary-ATP:AK complex (koff = 118.9 ± 36.3 s -1 and 693.4 ± 29.6 s -1 , respectively, Figure 2I, left).…”
Section: Allosteric Effects and Concerted Domain Motions Are Linked T...supporting
confidence: 76%
See 3 more Smart Citations
“…By contrast, ATP induces the closing of the LID domain, and the subsequent arrival of AMP induces the closing of the NMP domain. These observations suggest the existence of an endosteric effect whereas: the initial binding of AMP inhibits the binding of ATP, or the initial binding of AMP forms a less active conformation, as previously suggested, 51 or the ATP-induced closing of the LID domain induces the formation of a higher-affinity binding site for AMP. In the M2-ternary-AMP:ATP:AK complex, the LID domain is more tightly closed (Figure 2I, right) than in the M2-binary-ATP:AK complex (koff = 118.9 ± 36.3 s -1 and 693.4 ± 29.6 s -1 , respectively, Figure 2I, left).…”
Section: Allosteric Effects and Concerted Domain Motions Are Linked T...supporting
confidence: 76%
“…; when ATP and AMP or Ap5A are sampled, indicating that when both active sites are occupied the two domains cooperatively open and close. As previously suggested for the observed fast LID domain fluctuations, 51 these concerted motions might be instrumental to align the reactants in the proper conformation. A full kinetic scheme for the binding of ATP and AMP is shown in Figure 3.…”
Section: Lid and Nmp Domain Motions Induced By Ligandssupporting
confidence: 64%
See 2 more Smart Citations
“…It was found that fast domain movements assist reorienting the substrates following incorrect initial binding to the enzyme, allowing them to reach an optimal orientation for catalysis. To shed further light on this question, mutants with different degrees of substrate inhibition by AMP were studied, both biochemically and using smFRET spectroscopy (112). It was shown that inhibitory concentrations of AMP lead to a faster and more cooperative domain closure by ATP, pointing to an allosteric interaction between the domains of AK.…”
Section: Domain Closure In Adenylate Kinasementioning
confidence: 99%